KOMUNIKASI INSTRUKSIONAL GURU DALAM MENINGKATKAN MINAT MEMBACA DAN MENGHAFAL ALQURAN DI MAQDIS KOTA DURI KECAMATAN MANDAU KABUPATEN BENGKALIS - Husna Welly Angraini; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Education is an important element in creating a good quality, smart, damai, and democratic resourse. A good education can not be achieved without communication. Instructional communication is a part of education communication. It is a center of teaching and learning process. Teachers in Maqdis use it in the teaching and learning process. The purpose of this research is to find out instructional communication process and method taught by teachers.Writer uses qualitative method. Informants are 4 teachers and 4 students which are decided by purposive technique sampling. The 4 teachers are known as friendly, firm, and polite. While the students are vary. They are housewife, pediatric, and school student. All of them can memorize quran more than 1 juz in Maqdis. The object of this research are the teachers’ instructional method in improving student’s willingness in reading and memorize quran. Primary data are taken through interview and secondary data is the former research and journal. Data collecting technique are observation, interview, and documentation. To get the authenticity of the data, writer uses participation extention and triangulasi.The result shows us that communication process using non verbal symbol, which are mouth or tounge of the teacher who read the quran, and voice intonation should be clear to every student. This process is repeat over and over to make students memorize the quran. The use of media to support the instructional communication is used such as book/modul, and video. Instructional communication method taught by teachers in Maqdis are preaching, discussion/question and answer, assignment, tasmi’ and murajaah.Keyword: instructional communication, instructional communication process, instructional communication method.